gulandom THE IMPORTANCE OF THE FOREIGN LANGUAGE IN OUR COUNTRY: THE IMPORTANCE OF THE FOREIGN LANGUAGE IN OUR COUNTRY - Hamraqulova, Gulandom (Журнал иностранных языков и лингвистики, 2022)
In today's fast-paced world, science and technology are also growing rapidly. Development in every field is moving forward. In particular, great changes are taking place in science. Delivering each subject to students using new innovative pedagogical technologies is one of the main requirements of today's education. Especially after the adoption of the Resolution of the First President of the Republic of Uzbekistan Islam Abduganievich Karimov dated December 13, 2012 No. PP 1875, the attention to teaching and learning foreign languages in our country has increased.